JEJAK BAHASA TORAJA DALAM BAHASA KAILI: SEGUGUS REKAM JEJAK BAHASA AUSTRONESIA DI NUSANTARA (Kaili Language in Torajanese Language: A Trace of Austronesian Languages in the Archipelago) - Darmawati M.R. (SAWERIGADING, 2014)
Mystery of the kinship of languages in the archipelago is still being evaluated by linguists of Comparative Linguistics. This paper aimed to explore Torajanese language trace kinship in Kaili using Comparative Linguistics point of view or what commonly called Comparative Historical Linguistics based on Grimm (Grimm’s law) and Verner’s theory. In particular, this study aimed to find out how far footprint of Torajanese language in Kaili language and when the two languages separate from its proto language. Torajanese language and Kaili were chosen because of the results of previous study that claimed Kaili languages in Central Sulawesi was Torajanese language (West Toraja). The method used in this paper is lexicostatistics by comparing 200 Swadesh basic vocabulary of Kaili and Toraja. This study found that Torajanese and Kaili are different languages with kinship percentage rate of 42.5 %. This percentage is derived from the discovery of 85 cognate words between Kaili Toraja, through comparisons of both vowel sound changes, sound changes consonant, the addition of sound/syllable and removal of noise. Lexicostatistics analysis of the results obtained of these two languages were separated in 17 BC.